1997
DOI: 10.1161/01.atv.17.10.2250
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Streptozotocin-Induced Hyperglycemia on Lipid Profiles, Formation of Advanced Glycation Endproducts in Lesions, and Extent of Atherosclerosis in LDL Receptor-Deficient Mice

Abstract: Investigations into the mechanisms by which diabetes accelerates atherosclerosis have been hampered by the lack of suitable animal models. We hypothesized that streptozotocin-treated LDL receptor-deficient mice would be a good model of diabetic atherosclerosis because streptozotocin causes diabetes in the parent C57BL/6 strain and because in these mice diet-induced hypercholesterolemia leads to the formation of advanced atherosclerotic lesions throughout the aorta. Diabetes was induced in 18 mice by intraperit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
79
0
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 88 publications
(92 citation statements)
references
References 31 publications
9
79
0
1
Order By: Relevance
“…Glucose concentrations measured after a 16-h fast were higher in Bhmt ϩ/ϩ (158 Ϯ 6 mg/dl) than in Bhmt Ϫ/Ϫ mice (119 Ϯ 10 mg/dl, p Ͻ 0.05). Glucose values were at the high end of what have been reported for C57Bl mice (130 -218 mg/dl for a 4-h fast (25)(26)(27)(28)(29) and 90 -120 mg/dl for a 12-16 h fast (27,30)). …”
Section: Discussionmentioning
confidence: 54%
“…Glucose concentrations measured after a 16-h fast were higher in Bhmt ϩ/ϩ (158 Ϯ 6 mg/dl) than in Bhmt Ϫ/Ϫ mice (119 Ϯ 10 mg/dl, p Ͻ 0.05). Glucose values were at the high end of what have been reported for C57Bl mice (130 -218 mg/dl for a 4-h fast (25)(26)(27)(28)(29) and 90 -120 mg/dl for a 12-16 h fast (27,30)). …”
Section: Discussionmentioning
confidence: 54%
“…35 These findings were in contradistinction to the work of Reavan et al These investigators found that induction of diabetes by streptozotocin in LDL receptorϪ/Ϫ mice fed a high-fat diet over an extended time course did not result in acceleration of atherosclerosis. 36 We posit that the differences between these 2 study outcomes may be ascribed, at least in part, to the premise that at the aortic root, the degree of atherosclerosis that may be achieved is finite. Thus, especially over long time courses in Western diet-fed mice, differences between diabetic and nondiabetic groups may become less apparent as atherosclerosis in the nondiabetic animals continues to progress.…”
Section: Diabetes and Atherosclerosis: Other Models To Test The Impacmentioning
confidence: 99%
“…Hyperglycemia has been hypothesized to enhance atherosclerosis in NIDDM, but the specific contribution of hyperglycemia has been difficult to demonstrate in either population studies or animal models. [5][6][7][8] Moreover, hyperglycemia per se is unlikely to play a role in the development of atherosclerosis in individuals with IGT who usually demonstrate only modest postprandial hyperglycemia. Insulin resistance is frequently associated with a number of metabolic abnormalities such as obesity, hypertriglyceridemia, low HDL, and hypertension.…”
mentioning
confidence: 99%
“…When fed such diets, these mice develop extensive atherosclerosis in the vicinity of the aortic valve (as seen in other atherosclerosissusceptible strains of mice), as well as in the arch, thoracic, and abdominal regions of the aorta. 7,[23][24][25][26] These aortic plaques show many morphological similarities to human atherosclerotic lesions and consist of both fatty streaks and more advanced lesions. 7,25 Given the close phylogenetic relationship between the mouse and the rat, we presumed that a fructose-rich diet would also lead to IR in mice.…”
mentioning
confidence: 99%
See 1 more Smart Citation